Answer:
• g(1) = 25
• g(n) = g(n-1) -49
Explanation:
You can get a clue by filling in n=2 in the explicit formula:
g(2) = 25 -49(2-1) = 25 -49 = g(1) -49
The explicit formula is of the form for an arithmetic sequence:
g(n) = g(1) +d(n-1) . . . . where g(1) is the first term and d is the common difference
Of course, this translates to the recursive formula ...
• g(1) = g(1)
• g(n) = g(n-1) +d
Here you have g(1) = 25, and d = -49. Filling these into the recursive form, you get ...
• g(1) = 25
• g(n) = g(n-1) -49